TROP2 promotes PINK1-mediated mitophagy and apoptosis to accelerate the progression of senile chronic obstructive pulmonary disease by up-regulating DRP1 expression - Yipu Zhao; Zhengjie Wu (Experimental Gerontology, 2024)
Chronic obstructive pulmonary disease (COPD) is a chronic airway inflammatory disease characterised by irreversible airflow limitation. The elderly are a vulnerable population for developing COPD. With the growth of age, physiological degenerative changes occur in the thorax, bronchus, lung and vascular wall, which can lead to age-related physiological attenuation of lung function in the elderly, so the prevalence of COPD increases with age. Its pathogenesis has not yet been truly clarified. Mitophagy plays an important role in maintaining the stability of mitochondrial function and intracellular environment by scavenging damaged mitochondria. Currently, studies have shown that trophoblast antigen 2 (TROP2) expression is up-regulated in airway basal cells of patients with COPD, suggesting that TROP2 is involved in the progression of COPD. However, whether it is involved in disease progression by regulating mitochondrial function remains unclear. In this study, compared with non-smoking non-COPD patients, the expression of TROP2 in lung tissues of smoking non-COPD patients and patients with COPD increased, and TROP2 expression in patients with COPD was higher than that in smoking non-COPD patients. To further explore the role of TROP2, we stimulated BEAS-2B with cigarette smoke to construct an in vitro model. We found that TROP2 expression increased, whereas TROP2 silencing reversed the cigarette smoke extract-induced decrease in mitochondrial membrane potential, increased reactive oxygen species content, decreased adenosine triphosphate (ATP) production, increased inflammatory factor secretion and increased apoptosis. In addition, we searched online bioinformatics and screened the gene dynamin-related protein 1 (DRP1) related to mitophagy as the research object. Co-IP assay verified the binding relationship between DRP1 and TROP2. Further study found that TROP2 promoted mitophagy and apoptosis of BEAS-2B cells by up-regulating the expression of DRP1. In addition, PTEN-induced putative kinase 1 (PINK1) is a potential binding protein of DRP1, and DRP1 accelerated mitophagy and apoptosis of BEAS-2B cells by promoting the expression of PINK1. We established a COPD SD rat model by cigarette smoke exposure and LPS instillation and treated it by intraperitoneal injection of si-TROP2. The results showed that TROP2 silencing restored lung function and reduced the secretion of inflammatory factors in bronchoalveolar lavage fluid. In conclusion, TROP2 can be used as a new reference for COPD treatment.